Terlipressin for variceal bleeding induces large plasma sodium fluctuations in patients without cirrhosis. Issue 8 (October 2018) - Eriksen, Peter Lykke; Hartkopf-Mikkelsen, Anne Luise; Ott, Peter; Vilstrup, Hendrik; Aagaard, Niels Kristian
Background: Terlipressin is used as pharmacological treatment for variceal bleeding. The drug's physiological effect favours hyponatremia, and rapid changes in plasma sodium (PNa) may cause brain injury. Cirrhosis patients seem to be largely protected against this effect but patients without cirrhosis may not be so. Objective: The objective of this study was to examine whether terlipressin treatment of patients without cirrhosis leads to more serious fluctuations in PNa than in cirrhosis. Methods: In a retrospective cohort design, during a 39-month period, 11 patients with prehepatic portal hypertension and no cirrhosis and 134 patients with cirrhosis received a minimum cumulative terlipressin dose of 4 mg during at least 24 hours for variceal bleeding. The groups' PNa changes were compared. Results: During terlipressin, the non-cirrhotic patients developed a greater reduction in PNa [mean 8.3 (95% confidence interval (CI) 1.9–14.6) vs. 1.8 (1.0–2.7) mmol/l; p  = 0.048], a lower nadir PNa [129 (123–135) vs. 133 (132–134) mmol/l; p  = 0.06], and within 48 hours after terlipressin a greater increase in PNa [12.6 (3.4–21.7) vs. 2.3 (1.5–3.0) mmol/l; p  = 0.03]. Severe (>10 mmol/l change) hyponatriemia or PNa rebound were seen in 27% of these patients but in only 4% of those with cirrhosis ( p  = 0.02). One non-cirrhotic patient developed permanent brain damage. Conclusion: Terlipressin treatment of bleeding varices carries a high risk of potentially dangerous PNa fluctuations in patients with non-cirrhotic prehepatic portal hypertension.